Multicatheter Interstitial Brachytherapy Versus Stereotactic Radiotherapy with CyberKnife for Accelerated Partial Breast Irradiation: A Comparative Treatment Planning Study with Respect to Dosimetry of Organs at Risk - Herein, András (Radiol Oncol, 2021)
BACKGROUND: The aim of the study was to dosimetrically compare multicatheter interstitial brachytherapy (MIBT) and stereotactic radiotherapy with CyberKnife (CK) for accelerated partial breast irradiation (APBI) especially concerning the dose of organs at risk (OAR-s). PATIENTS AND METHODS: Treatment plans of thirty-two MIBT and CK patients were compared. The OAR-s included ipsilateral non-target and contralateral breast, ipsilateral and contralateral lung, skin, ribs, and heart for left-sided cases. The fractionation was identical (4 x 6.25 Gy) in both treatment groups. The relative volumes (e.g. V100, V90) receiving a given relative dose (100%, 90%), and the relative doses (e.g. D0.1cm(3), D1cm(3)) delivered to the most exposed small volumes (0.1 cm(3), 1 cm(3)) were calculated from dose-volume histograms. All dose values were related to the prescribed dose (25 Gy). RESULTS: Regarding non-target breast CK performed slightly better than MIBT (V100: 0.7% vs. 1.6%, V50: 10.5% vs. 12.9%). The mean dose of the ipsilateral lung was the same for both techniques (4.9%), but doses irradiated to volume of 1 cm(3) were lower with MIBT (36.1% vs. 45.4%). Protection of skin and rib was better with MIBT. There were no significant differences between the dose-volume parameters of the heart, but with MIBT, slightly larger volumes were irradiated by 5% dose (V5: 29.9% vs. 21.2%). Contralateral breast and lung received a somewhat higher dose with MIBT (D1cm(3): 2.6% vs. 1.8% and 3.6% vs. 2.5%). CONCLUSIONS: The target volume can be properly irradiated by both techniques with similar dose distributions and high dose conformity. Regarding the dose to the non-target breast, heart, and contralateral organs the CK was superior, but the nearby organs (skin, ribs, ipsilateral lung) received less dose with MIBT. The observed dosimetric differences were small but significant in a few parameters at the examined patient number. More studies are needed to explore whether these dosimetric findings have clinical significance.